Association of the gut microbiota with coronary artery disease and myocardial infarction: A Mendelian randomization study - Wang, Dan; Chen, Xiaoyan; Li, Zhen; Luo, Ying (Frontiers in Genetics, 2023)
Background: Previous studies have indicated that the gut microbiota (GM) is associated with coronary artery disease (CAD), but the causality of these associations remains unestablished due to confounding factors and reverse causality. We conducted a Mendelian randomization study (MR) to determine the causal effect of the GM on CAD/myocardial infarction (MI) and identify specific causal bacterial taxa to find more potential prevention and treatment targets. Methods: A two-sample MR study was performed. Inverse-variance weighting (IVW) was the main method used to analyse causality, and sensitivity analysis was used to verify the reliability of the study. Causal estimates from CARDIoGRAMplusC4D and FinnGen databases were combined using the meta-analysis method, and repeated validation was conducted based on the UK Biobank (UKB) database. Results: The study suggested that increased abundance of the RuminococcusUCG010 genus leads to a lower risk of CAD (OR, 0.88; 95% CI, 0.78, 1.00; p = 2.88 × 10-2) and MI (OR, 0.88; 95% CI, 0.79, 0.97; p = 1.08 × 10-2), with consistent results in both meta-analysis (CAD: OR, 0.86; 95% CI, 0.78, 0.96; p = 4.71 × 10−3; MI: OR, 0.82; 95% CI, 0.73, 0.92; p = 8.25× 10−4) and repeated analysis of the UKB dataset ( CAD: OR, 0.99; 95% CI, 0.99, 1.00, p = 2.53 × 10-4; MI: OR, 0.99; 95% CI, 0.99, 1.00, p = 1.85 × 10-11). Conclusion: This MR study provided suggestive genetic evidence that the higher the RuminococcusUCG010 abundance is, the lower the risk of CAD and MI. This genus may become a novel target in strategies for treating and preventing CAD and MI.